The crucial centres: Water production and well efficiency in Borana - Cossins, N.J. (International Livestock Centre for Africa, 1983)
Presents results of a study on existing water production methods, the rate & amount of production and inefficiencies & production losses; importance of "okoles" (leather buckets) in relation to output rates & okole sizes and their supply; influence of "tetchana" (holding pond after shaft) and "Maninga" (watering trough) on output rates & well efficiency; and energy expenditure of well workers, and labour demand & availability in group wells in the Borana plateau in the southern rangelands of Ethiopia.